Tricaine, eugenol and etomidate for repetitive procedural anesthesia in adult zebrafish, Danio rerio: effect on stress and behavior - Narumanchi, Suneeta; Perttunen, Sanni; Laine, Pyry; Kosonen, Riikka; Lakkisto, Päivi; Laine, Mika; Tikkanen, Ilkka; Paavola, Jere (Frontiers in Veterinary Science, 2025)
Zebrafish has emerged as a popular animal model in biomedical research. Numerous procedures and interventions require occasionally repetitive anesthesia. Tricaine is the most frequently used anesthetic for zebrafish and its efficacy is well established. However, the safety and efficacy of other anesthetics used for zebrafish require further examination, especially regarding repetitive anesthesia. Hence, we compare three anesthetics: tricaine (150 mg/l), eugenol (55 mg/l) and etomidate (4 mg/l) in wildtype adult zebrafish with and without interventions in the form of intraperitoneal injections. Groups of fish receiving the injections are named as (+ injection). We quantify anesthesia induction and recovery times as well as swimming behavior and cortisol levels as indicators of stress. Swimming behavior is quantified with the novel tank method as tank preference and number of turnings. Adult zebrafish are randomly divided into seven groups; tricaine (n = 15), tricaine (+injection; n = 15), eugenol (n = 15), eugenol (+injection; n = 14), etomidate (n = 15), etomidate (+injection; n = 15) and sham (n = 10), and anesthetized until they reach stage 4 anesthesia, daily for 10 days. Following anesthesia induction, injection groups are given daily intraperitoneal injections with 0.9% saline (4 ml/kg) before transfer to a recovery tank to study the effect of a painful procedure (the intraperitoneal injection) during anesthesia on stress. The novel tank method is used for analyzing behavior at day 2 (beginning), day 5/6 (middle) and day 10 (end). Chronic stress is evaluated by whole-body cortisol measurement at the end of the 10-day experiment. Additionally, acute stress is evaluated by whole-body cortisol measurement 30 min after single anesthesia in five groups: tricaine (n = 5), eugenol (n = 5), etomidate (n = 5), sham (n = 5), and untreated controls (n = 5). We find that fish anesthetized with tricaine recover fast (~ 1.5 min) and show normal swimming behavior. Fish anesthetized with eugenol show recovery time (~ 2.5 min) and swimming behavior similar to that of fish receiving tricaine. Fish anesthetized with etomidate have the longest recovery time (~ 5.5 min) and exhibit stressed swimming behavior. Cortisol levels remain at similar levels. Our study supports the use of tricaine as the anesthetic-of-choice for repetitive anesthesia of short duration in zebrafish, followed by eugenol.